1990
DOI: 10.1111/j.1755-3768.1990.tb04797.x
|View full text |Cite
|
Sign up to set email alerts
|

Apparent accommodation in pseudophakic eyes

Abstract: The so-called apparent accommodation has been measured in patients implanted with anterior chamber, iris support and posterior chamber IOLs. The data have been related to pupillary diameter and anterior chamber depth in order to explain the actual possibility of a near vision with optical correction only for distance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…8,9 However, it has been shown that patients with monofocal IOLs have a certain range of apparent accommodation. [10][11][12][13] Accordingly, it would be better to fully use the region of apparent accommodation.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…8,9 However, it has been shown that patients with monofocal IOLs have a certain range of apparent accommodation. [10][11][12][13] Accordingly, it would be better to fully use the region of apparent accommodation.…”
Section: Discussionmentioning
confidence: 98%
“…Accordingly, it is now advantageous, or almost essential, that both near and intermediate distance tasks be performed; this capability can be met by using the region of apparent accommodation. [10][11][12][13] Studies show that slight myopia accompanied by a certain degree of astigmatism enhances the depth of focus in eyes with a monofocal IOL. [14][15][16][17] It is difficult, however, to produce the optimum degree of astigmatism after cataract surgery, whereas small-incision cataract surgery affects astigmatism only slightly.…”
mentioning
confidence: 98%
“…21,22 Increased levels of pseudoaccommodation may be used to increase the depth of focus and accommodative amplitude in the presbyopic population. The most frequent factors that positively influence pseudoaccommodation include corneal and IOL wavefront aberration, astigmatism, [23][24][25][26][27] and small pupil size. 25 Based on the understanding of inherent pseudoaccommodation, these pseudoaccommodative mechanisms are employed in different types of the EDOF lenses.…”
Section: Introductionmentioning
confidence: 99%
“…22,23 Anatomic changes during accommodation, particularly of the anterior segment, have been successfully demonstrated by US imaging in presbyopic eyes as well as after cataract surgery. [24][25][26] The effects of ciliary muscle contraction in pseudophakic eyes have also been reported. 24,27 In 2000, Lesiewska-Junk and Ka1un _ zny 28 reported anterior IOL shift caused by accommodative stimuli in young pseudophakic eyes.…”
mentioning
confidence: 95%